If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-1b + -4) = -1(b + -8) Reorder the terms: -2(-4 + -1b) = -1(b + -8) (-4 * -2 + -1b * -2) = -1(b + -8) (8 + 2b) = -1(b + -8) Reorder the terms: 8 + 2b = -1(-8 + b) 8 + 2b = (-8 * -1 + b * -1) 8 + 2b = (8 + -1b) Add '-8' to each side of the equation. 8 + -8 + 2b = 8 + -8 + -1b Combine like terms: 8 + -8 = 0 0 + 2b = 8 + -8 + -1b 2b = 8 + -8 + -1b Combine like terms: 8 + -8 = 0 2b = 0 + -1b 2b = -1b Solving 2b = -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. 2b + b = -1b + b Combine like terms: 2b + b = 3b 3b = -1b + b Combine like terms: -1b + b = 0 3b = 0 Divide each side by '3'. b = 0 Simplifying b = 0
| 8.7x+4.42=-11.3x+3.18 | | 6+4w=13+3w | | -8(x+7)+5=-51 | | 4r+6=13+2r | | x*2+4*x+y*2-21=0 | | ln(4x^6+2x^3)=y | | 180=120x | | -2(b-4)=-(b-8) | | x^2+1-11=0 | | 4xn+2=10+2n | | 20w^2+10w+40=0 | | 16x^2-96x+4y^2+8y=-84 | | 96j+245=53 | | log(2)18=x | | 12x+9-5x^2=0 | | -8x+9x=-2 | | 5n+1=2n+3 | | 6.7x-3.4=16.7 | | 5x-9+4x=3x+30 | | 7p-23=-17+8p | | 2v+7=5v+4 | | 45=360+x | | 2r-16=-6+4r | | 4g+20=10g+5 | | Y=8sec(5x) | | 2(x-7)-9=-23 | | 5(3x+2)=7 | | 3n+2=1n+12 | | (x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106 | | 2x^4=35 | | 1n+9=4n+3 | | -16x^2+240x+20=0 |